The Lamu Basin deepwater fold‐and‐thrust belt: An example of a margin‐scale, gravity‐driven thrust belt along the continental passive margin of East Africa. Issue 3 (3rd March 2016) - Cruciani, Francesco; Barchi, Massimiliano R.
Abstract: In recent decades, advances in seismic processing and acquisition of new data sets have revealed the presence of many deepwater fold‐and‐thrust belts (DW‐FTBs), often developing along continental passive margins. These kinds of tectonic features have been intensively studied, due to their substantial interest. This work presents a regional‐scale study of the poorly explored Lamu Basin DW‐FTB, a margin‐scale, gravity‐driven system extending for more than 450 km along the continental passive margin of Kenya and southern Somalia (East Africa). A 2‐D seismic data set was analyzed, consisting of both recently acquired high‐quality data and old reprocessed seismic profiles, for the first detailed structural and stratigraphic interpretation of this DW‐FTB. The system originated over an Early to mid‐Cretaceous shale detachment due to a mainly gravity‐spreading mechanism. Analysis of synkinematic strata indicates that the DW‐FTB was active from the Late Cretaceous to the Early Miocene, but almost all of the deformation occurred before the Late Paleocene. The fold‐and‐thrust system displays a marked N‐S variation in width, the northern portion being more than 150 km wide and the southern portion only a few dozen kilometers wide; this along‐strike variation is thought to be related to the complex tectonosedimentary evolution of the continental margin at the Somalia‐Kenya boundary, also reflected in the present‐day bathymetry. Locally, a series of volcanic edifices stopped the basinward propagation of the DW‐FTB. A landward change in the dominant structural style, from asymmetric imbricate thrust sheets to pseudo‐symmetric detachment folds, is generally observed, related to the landward thickening of the detached shales. Key Points: A margin‐scale, gravity‐driven thrust belt affects the offshore Lamu Basin Structural style shows remarkable variations along strike and along dip Structural style depends on the thickness of detached shales